1991
DOI: 10.1007/bf02100199
|View full text |Cite
|
Sign up to set email alerts
|

The main regulatory region of mammalian mitochondrial DNA: Structure-function model and evolutionary pattern

Abstract: The evolution of the main regulatory region (D-loop) of the mammalian mitochondrial genome was analyzed by comparing the sequences of eight mammalian species: human, common chimpanzee, pygmy chimpanzee, dolphin, cow, rat, mouse, and rabbit. The best alignment of the sequences was obtained by optimization of the sequence similarities common to all these species. The two peripheral left and right D-loop domains, which contain the main regulatory elements so far discovered, evolved rapidly in a species-specific m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
190
1
7

Year Published

1995
1995
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(206 citation statements)
references
References 20 publications
4
190
1
7
Order By: Relevance
“…Saunders and Edwards (2000) studied dynamics and phylogenetic implications of mtDNA CR sequences in the New World Jays and found a slow rate of evolution in the CR. They suggested that their data indicated a higher Studies have showed that CR contains sequences related to termination of H-strand replication, the origin of H-strand, and promoters of transcription to both L-and H-strand (Doda et al, 1981;Randi and Lucchini, 1998;Saccone et al, 1991;Sbisà et al, 1997;Southern et al, 1988). This indicates that the CR has evolutionary constraints.…”
Section: Dynamics Of the Evolutionary Rate Of Crmentioning
confidence: 98%
“…Saunders and Edwards (2000) studied dynamics and phylogenetic implications of mtDNA CR sequences in the New World Jays and found a slow rate of evolution in the CR. They suggested that their data indicated a higher Studies have showed that CR contains sequences related to termination of H-strand replication, the origin of H-strand, and promoters of transcription to both L-and H-strand (Doda et al, 1981;Randi and Lucchini, 1998;Saccone et al, 1991;Sbisà et al, 1997;Southern et al, 1988). This indicates that the CR has evolutionary constraints.…”
Section: Dynamics Of the Evolutionary Rate Of Crmentioning
confidence: 98%
“…Replication of insect mtDNA is extremely asymmetric. Since the structure of the control region in mammals/chordates (Sbisá et al, 1997;Saccone et al, 1991) and insects (Saito et al, 2005;Zhang and Hewitt, 1997) is very different it is unclear at present whether the same mechanisms are responsible for initiation and termination of replication throughout the Metazoa.…”
Section: Model(s) Of Replicationmentioning
confidence: 99%
“…It is widely used for genetic inferences especially in mammals where it is also known as the D-loop (for displacement-loop), a three-stranded structure that forms during replication of the molecule. At least in vertebrates, functional structures within this region have been identified across a wide number of species namely highly conserved sequences associated with the molecule replication, conserved and variable blocks, as well as palindromic and stable cloverleaf structures that may be involved in the replication of the molecule as well as transcription initiation sites for each strand (Chang and Clayton 1984;Saccone et al 1991;Clayton 1982Clayton , 1996. In invertebrates, the control region is much less studied and understood.…”
Section: Introductionmentioning
confidence: 99%